Perception of domestic risks among carers for dependent older persons. Issue 5 (10th July 2018) - Monfort, Emmanuel; Gandit, Marc; Poulet, Caroline; Quillion‐Dupré, Lisa; Boudin, Bertrand; Couturier, Pascal
Abstract : Background: Despite growing interest for home care, little evidence exists on the perception of domestic risk among carers for dependent older persons. This study aims to characterize the risks to which carers of aging dependent individuals are exposed, and to determine whether these risk dimensions are predictive for effective support, for burden, and for psychological distress. Methods: Seventy care partners were questioned about the risk situations identified at the homes of the old people they care for, about the burden they felt in their role, and about their feelings of psychological distress. Securing was evaluated by means of sensibility measures, and overprotection was evaluated by means of specificity measures. Results: Risk rates were high for loneliness of the old people, wandering, burns, and unsatisfactory health monitoring. There was very little overlap between identification of the risks and implementation of solutions by the caregiver, except for the risks that involved heat. The distinction between accurate securing and overprotection is especially important, because the burden of care partners was linked to uncontrolled domestic risks. Conclusion: Typologies of reactions to risk, characterized by a signal detection approach, could contribute to a better understanding of the situations experienced by care partners, especially situations of neglect and of overprotection.